2001
DOI: 10.1248/bpb.24.151
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Inhibitory Effect of Oral Shark Cartilage on Basic Fibroblast Growth Factor-Induced Angiogenesis in the Rabbit Cornea.

Abstract: Angiogenesis is a multistep and redundant process crucial in several physiological events and pathophysiological developments such as cancer. Since the early findings by Folkman et al. that tumor growth is dependent on new vascularization, it is now broadly accepted that solid tumors cannot grow beyond 1-2 mm without a vascular supply of oxygen and nutrients.1) Further, there is a substantial body of evidence indicating that attacking tumor neovascularization is a promising approach in the treatment of cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Therefore, corneal neovascularisation induced through two intrastromal implantations of VEGF polymer serves as a suitable animal model for the study of inflammatory corneal neovascularization. There are a number of natural products known to possess antiangiogenic properties which include genistein [22], shark cartilage [23], curcumin [24,25], propolis extract [26] and AME [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, corneal neovascularisation induced through two intrastromal implantations of VEGF polymer serves as a suitable animal model for the study of inflammatory corneal neovascularization. There are a number of natural products known to possess antiangiogenic properties which include genistein [22], shark cartilage [23], curcumin [24,25], propolis extract [26] and AME [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…8 For this reason, many therapeutic agents generated to block growth factor-induced angiogenesis are now in clinical trials. 9,10 Among the integrin family members most widely studied in the angiogenic process are of the ␣ v family-integrins ␣ v ␤ 3 and ␣ v ␤ 5 , which are receptors for vitronectin. 4,[11][12][13] These 2 integrins regulate 2 distinct pathways of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that oral administration of shark cartilage and its extracts suppress carcinogenesis, growth of tumor, , and also angiogenesis in animal models. Angiogenesis is the formation of new capillaries from the established veins, which plays significant role in tumor growth and carcinogenesis .…”
Section: Introductionmentioning
confidence: 99%